2019
DOI: 10.1103/physrevx.9.031040
|View full text |Cite
|
Sign up to set email alerts
|

GWTC-1: A Gravitational-Wave Transient Catalog of Compact Binary Mergers Observed by LIGO and Virgo during the First and Second Observing Runs

Abstract: We present the results from three gravitational-wave searches for coalescing compact binaries with component masses above 1 M ⊙ during the first and second observing runs of the advanced gravitationalwave detector network. During the first observing run (O1), from September 12, 2015 to January 19, 2016, gravitational waves from three binary black hole mergers were detected. The second observing run (O2), which ran from November 30, 2016 to August 25, 2017, saw the first detection of gravitational waves from a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

103
3,208
5
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,225 publications
(3,446 citation statements)
references
References 254 publications
103
3,208
5
4
Order By: Relevance
“…• For the merger events detected so far by LIGO-Virgo, the effective spin parameter of the binary is compatible to zero, except possibly for few high-mass events [3,4,[20][21][22]. We have shown that a primordial origin of these BH binaries could naturally explain this distribution, especially in the likely scenario in which accretion is quenched at z 10 due to structure formation [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• For the merger events detected so far by LIGO-Virgo, the effective spin parameter of the binary is compatible to zero, except possibly for few high-mass events [3,4,[20][21][22]. We have shown that a primordial origin of these BH binaries could naturally explain this distribution, especially in the likely scenario in which accretion is quenched at z 10 due to structure formation [41].…”
Section: Resultsmentioning
confidence: 99%
“…where M 1 and M 2 are the individual BH masses, J 1 and J 2 are the corresponding angularmomentum vectors, andL is the direction of the orbital angular momentum. From the observational point of view, there is a general tendency for the effective spin parameter of merger events detected so far to be compatible with zero [3,4], with possible few exceptions [4,[20][21][22] of high-mass events (total mass larger than 50 M ). The available data indicates that the dispersion of χ eff around zero grows with the mass [23].…”
Section: Introductionmentioning
confidence: 99%
“…The detection of gravitational waves (GWs) by the LIGO and VIRGO collaborations [1][2][3][4][5][6][7][8][9] from a merging of a pair of heavy black holes seems to be consistent with a prediction of Einstein's general relativity. The GW due to the merging of a neutron star pair has also been observed subsequently [10,11], opening new possibilities for astronomical observation and cosmological research.…”
Section: Introductionmentioning
confidence: 97%
“…Gravitational-wave astronomy, started in 2015 with the first detection of a black hole merger by LIGO [1], has rapidly become a mature research field. After the groundbreaking observation of the binary neutron star coalescence GW170817 [2]and the publication of the first gravitational-wave sources catalog [3], the network of advanced interferometric detectors (comprised of the two Advanced LIGO [4] and Advanced Virgo [5]) is now performing a third period of data taking (O3), detecting several candidates per month and sending open alerts to the astronomical community [6]. The Japanese detector, KAGRA [7], is about to join the network and is expected to be followed by a fifth detector, LIGO India, in 2024 [8].…”
Section: Introductionmentioning
confidence: 99%